Atomic data on inelastic processes in boron–hydrogen collisions with accounting for fine structure. Issue 1 (12th January 2023) - Voronov, Yaroslav V; Yakovleva, Svetlana A; Belyaev, Andrey K
ABSTRACT: This paper reports the results of investigations of inelastic processes in B + H and B + + H − collisions with accounting for the fine structure. The calculations of the cross-sections and rate coefficients for excitation, de-excitation, ion-pair formation, and mutual neutralization processes (240 in total) are performed by using the quantum asymptotic method, which is modified in this paper for accounting of the fine structure, and by the multichannel approach within the framework of the Born–Oppenheimer formalism. It is found that accounting for the fine structure may change the rate coefficients significantly, and the rates calculated with accounting for the fine structure cannot be obtained by a simple redistribution of the non-relativistic rates. The processes important for non-local thermodynamic equilibrium modelling of stellar atmospheres are designated.